Sustainability-related transgressions in global supply chains: When do legitimacy spillovers hurt buying firms the most? - Ivana Mateska; Christian Busse; Andrew P. Kach; Stephan M. Wagner (Journal of Supply Chain Management, 2023)
In a globalized world, buying firms increasingly face criticism regarding sustainability-related transgressions in their supply chains, yet scholarship concerning whether such negative press has any bottom-line effects has only just begun emerging. This study develops and tests theory on the relationship between reported supplier sustainability incidents and the associated stock price impact for the buying firm. An event study comprising 1699 events related to 374 buying firms supports our hypothesis that media coverage of environmental, social, or governance-related transgressions in the supply chain results in decreased market capitalization for the buying firm. A subsequent regression analysis indicates that the influence potential of information intermediaries, the country-level sustainability risk of the supplier, and the industry-level sustainability risk of the buying firm all affect the magnitude of the investors' reaction. Conversely, the severity of the incident does not predict the magnitude of the stock price reaction.
Keywords: 330; complicity; event study; legitimacy spillover; stakeholder theory; supply chain management; sustainability risk